PRELIMINARY PHYTOCHEMICAL SCREENING OF SIX MEDICINAL PLANTS USED AS TRADITIONAL MEDICINE - U.S.PATIL; O. S.DESHMUKH (International Journal of Pharma and Bio Sciences, 2016)
Preliminary screening of phytochemicals is a valuable step, in the detection of the bioactive principles present in medicinal plants and subsequently may lead to drug discovery and development. In the present study, chief phytoconstituents of the six selected medicinal plants of different families were identified in order to relate their presence with bioactivities of the plants. Screening of six selected medicinal plants were performed for the presence of tannins, flavonoids, terpenoids, saponins, steroids, phlobatannins, carbohydrates, glycosides, coumarins, alkaloids, proteins, emodins and anthraquinones using standard methods. All the selected medicinal plants were found to contain Steroids and Coumarins except Urginea indica (Roxb.) Kunth and Wrightia tinctoria R.Br.respectively. Moreover, tannins and terpenoids were present only in Spatholobus purpureus Hassk. On the other hand, saponins were present in Terminalia bellirica L., Parthenocissus quinquefolia L. and Spatholobus purpureus Hassk. Carbohydrate were present in Wrightia tinctoria R.Br. and Spatholobus purpureus Hassk. plants. While alkaloids are present in Cyclea peltata Arn. ex Wight and Wrightia tinctoria R.Br. Whereas phlobatannins, emodins and glycosides were absent in all the selected six plants. It is evident from the study that Spatholobus purpureus Hassk. and Wrightia tinctoria R.Br. is of highest therapeutic efficacy possessing majority of phytochemical classes of compounds and Urginea indica (Roxb.) Kunth is of lowest therapeutic potential due to the absence of majority of phytoconstituents.